2004
DOI: 10.1063/1.1835555
|View full text |Cite
|
Sign up to set email alerts
|

Operating characteristics of a traveling-wave semiconducting polymer optical amplifier

Abstract: We report a study of light amplification in dilute solutions of the semiconducting polymer poly(9,9-dioctylfluorene-co-benzothiadiazole) (F8BT). The operating characteristics of the F8BT solution amplifier are investigated in detail, and we show that it provides a large optical gain (>40dB∕cm) across a wide (>48nm) spectral bandwidth in the green. The saturation characteristics of the amplifier are found to be in excellent agreement with theoretical predictions, allowing an estimate of the F8BT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A maximum gain of 5.5 cm −1 and 4.2 cm −1 is found in LDS 720‐based and IR 140‐based fibers, respectively, making them suitable systems for the potential implementation of nanolaser sources and optical amplifiers assisted by the fiber waveguiding properties . These values have to be related to the local excitation conditions and orientation of transition dipoles in the different electrospun materials.…”
Section: Resultsmentioning
confidence: 99%
“…A maximum gain of 5.5 cm −1 and 4.2 cm −1 is found in LDS 720‐based and IR 140‐based fibers, respectively, making them suitable systems for the potential implementation of nanolaser sources and optical amplifiers assisted by the fiber waveguiding properties . These values have to be related to the local excitation conditions and orientation of transition dipoles in the different electrospun materials.…”
Section: Resultsmentioning
confidence: 99%
“…Such structures provide an elegant way of tuning the wavelength of the output emission by altering the supported resonance frequency through control of the grating dimensions and/or the blend film thickness. [31][32][33][34][35] Fig. 4(a) shows a typical, peak intensity normalised, laser spectrum (659 nm peak) for a 250 nm thickness, 15 wt.…”
Section: Distributed Feedback Laser Characteristicsmentioning
confidence: 99%
“…22,34,35 F8BT also has a suitable lowest unoccupied molecular orbital (LUMO) for relative ease of electron injection and is a good electron transport material, 36 complementing the highest occupied molecular orbital (HOMO) alignment for efficient hole injection from standard anode materials combined with good hole transport properties that are typical of polythiophenes. 2 Another advantage of the RR-P3HT/F8BT blend system is that both components are readily commercially available, unlike a number of other polymers including Red F; a situation that will allow the system to be more widely utilised.…”
Section: Introductionmentioning
confidence: 99%
“…Detection occurs when the high electron affinity nitroaromatic analytes bind to the polymer surface introducing nonradiative deactivation pathways 2 that quench the fluorescence by an electron transfer mechanism. CPs have already been demonstrated to exhibit strong optical amplification 7,8 and are highly promising laser materials. [9][10][11] Rose et al 5 have shown that microring lasers based on a poly͑pphenylene vinylene͒ derivative can have enhanced sensitivity for the detection of explosive vapors when operated close to threshold.…”
mentioning
confidence: 99%